Dealcoholized Muscadine Wine Alleviates Inflammation and Preserves Intestinal Barrier in Il-10−/− Mice With Spontaneous Colitis. (7th June 2021) - Li, Hao; Wang, Gary; Sidhu, Gurjit; Yagiz, Yavuz; Gu, Liwei
Abstract: Objectives: Muscadine wine has a unique polyphenol profile consisting of anthocyanin 3, 5-diglucosides, ellagitannins, ellagic acids, and flavonols. This study aimed to determine whether dealcoholized muscadine wine (DMW) alleviated inflammatory bowel diseases (IBD) in IL-10 −/− mice. Methods: DMW was prepared by concentrating muscadine wine to 10% of its original volume. Male IL-10 −/− and wild-type C57BL/6 mice (6∼7-week-old) were fed an AIN-93M diet containing DMW (5.5%, v/w) or wine-free diet for 154 days. Body weight, food intake, stool consistency, rectum bleeding, and disease activity index of mice were recorded twice a week. Colon, spleen, and serum were collected after euthanasia for histological and biochemical analysis. Fluorescence of serum were measured 4 hours after oral gavage of fluorescein isothiocyanate (FITC)-dextran to determine the intestinal permeability. Results: IL-10 −/− mice developed ulcerative colitis, inflammation, and impaired gut barrier spontaneously whereas wild type mice remained healthy. DMW in diet preserved colon length and decreased colon histology score by 21.2% in IL-10 −/− mice ( P  < 0.05). IL-10 −/− mice on DMW diet had a significantly lower disease activity index than those on wine-free diet. Serum level of keratinocyte chemokine, IL-1β, and TNF-α were decreased by 31.8%, 62.8%, and 29.3% ( P  < 0.05), respectively, by DMW in IL-10 −/− mice, whereas IL-6 remained unchanged. Compared to the wine-free diet, concentration of FITC-dextran in the serum of IL-10 −/− mice were decreased by 18% by DMW ( P  < 0.05), indicating improved intestinal barrier function. DMW had no effect on wild type mice. IL-10 −/− mice had comparable body weight to wild type ones although their overall food intake was lower. Conclusions: DMW alleviated colon inflammation via inhibiting the secretion of inflammatory cytokines and preserving intestinal barrier. Muscadine wine has a potential to manage IBD in patients. Funding Sources: This research is supported by NIFA 2018–07, 941.